2008
DOI: 10.1007/s10151-008-0405-y
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial comparing LigaSure haemorrhoidectomy with open diathermy haemorrhoidectomy

Abstract: ated on. LigaSure haemorrhoidectomy had a significantly lower mean operative time and intraoperative bleeding. At 3 weeks after surgery, haemorrhoidectomy performed with LigaSure had an odds ratio for complete epithelialization of 3.1 over diathermy (95% CI 1.2-8.2). There was no difference in postoperative pain. Conclusions LigaSure haemorrhoidectomy is superior to diathermy for open haemorrhoidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
19
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 10 publications
(13 reference statements)
5
19
1
1
Order By: Relevance
“…Complete wound healing was achieved in *85% of patients by 4 weeks and reached 100% by 6 weeks, while after OH 60% healed by 4 weeks and it was only after 8 weeks that the wounds of all patients were completely healed. In accordance with our findings, Tan et al [17] reported that by 4 weeks after surgery 95% of LH, wounds had healed completely, compared to 76% of OH wounds. Other authors have reported similar results [10,13,18].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Complete wound healing was achieved in *85% of patients by 4 weeks and reached 100% by 6 weeks, while after OH 60% healed by 4 weeks and it was only after 8 weeks that the wounds of all patients were completely healed. In accordance with our findings, Tan et al [17] reported that by 4 weeks after surgery 95% of LH, wounds had healed completely, compared to 76% of OH wounds. Other authors have reported similar results [10,13,18].…”
Section: Discussionsupporting
confidence: 94%
“…The present study showed, as other studies have [10,[17][18][19], that after LH, return to work and normal activities was significantly faster than after conventional OH owing to reduced postoperative pain and faster wound healing. This, in addition to reduced operative time, may compensate for the higher cost of the LigaSure electrodes, particularly since reduced pain did not lead to a shorter hospital stay.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Bessa found that postoperative pain in the first week after LH was significantly lower than conventional hemorrhoidectomy [12] . Two other studies found that although early (<3 days), postoperative pain after LH was lower; this difference faded in long-term (>7 days) follow-up [13,14] . In our study, although VAS scores on the first postoperative day in both groups were not significantly different, third-day values were in favour of the MMH technique, which was statistically significant.…”
Section: Discussionmentioning
confidence: 99%